2017
DOI: 10.1002/adma.201704961
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Nearly 30% External Quantum Efficiency for Orange–Red Organic Light Emitting Diodes by Employing Thermally Activated Delayed Fluorescence Emitters Composed of 1,8‐Naphthalimide‐Acridine Hybrids

Abstract: The combination of rigid acridine donor and 1,8-naphthalimide acceptor has afforded two orange-red emitters of NAI-DMAC and NAI-DPAC with high rigidity in molecular structure and strongly pretwisted charge transfer state. Endowed with high photoluminescence quantum yields (Φ ), distinct thermally activated delayed fluorescence (TADF) characteristics, and preferentially horizontal emitting dipole orientations, these emitters afford record-high orange-red TADF organic light-emitting diodes (OLEDs) with external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
268
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 515 publications
(282 citation statements)
references
References 48 publications
14
268
0
Order By: Relevance
“…We have described the synthesis and characterization of novel twistacene-modified D-p-A chromophores (2)(3)(4)(5). On the basis of the DFT and experimental analysis, twistacene can act as an electron reservoir.W ith enhanced electron-withdrawing ability and elongated conjugation length, the as-prepared molecules exhibit strongf luorescence from blue to cyan, and then orange.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have described the synthesis and characterization of novel twistacene-modified D-p-A chromophores (2)(3)(4)(5). On the basis of the DFT and experimental analysis, twistacene can act as an electron reservoir.W ith enhanced electron-withdrawing ability and elongated conjugation length, the as-prepared molecules exhibit strongf luorescence from blue to cyan, and then orange.…”
Section: Resultsmentioning
confidence: 99%
“…At present, OLEDsb ased on metal-free thermallya ctivated delayed fluorescence (TADF) materials have received growingi nterest for their possibility to generate 100 %i nternal quantum efficiency by the up-conversionf rom the nonradiative triplet states to the radiatives inglets tates. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Moreover,t he performance of certain TADF materials could compare with those of the phosphorescent OLEDs,a long with low costs and abun-dant resources. As the core building block of the desired compounds is responsible for the optoelectronic properties and molecular stability,t he rational designa nd functionalization of the core building blocks are of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the turn-on voltage at 1cdm À2 is distinctly reduced from 3.8 V to 3.2 Va fter the device optimization (see Figure S12 and Table 2). Correspondingly,the maximum luminous efficiency, power efficiency, and EQE are improved from 36.9 cd A À1 , 24.1 lm W À1 ,a nd 12.3 %t o6 8.8 cd A À1 ,6 0.0 lm W À1 ,a nd 23.5 %, respectively.T he obtained EQE approaches the theoretical limit of 23.8 %n ow,w hich suggests that the PFI modification is beneficial for balanced charge injection and transporting.M oreover,i tr emains as high as 18.0 %e ven at ah igh luminance of 1000 cd m À2 ,i ndicative of the small efficiency roll-off.T aking advantage of the efficient greenishblue emission of poly(AcBPCz-TMP), an orange-red TADF emitter NAI-DMAC [10] is further doped into the EML. A warm white EL is realized (Figure 6b;see Figure S13), giving ar ecord-high EQE of 20.9 %( 61.1 cd A À1 ,5 6.4 lm W À1 )a s well as CIE coordinates of (0.36, 0.51).…”
Section: Electroluminescence Propertiesmentioning
confidence: 99%
“…Thermally activated delayed fluorescence (TADF) emitters,following the conventional fluorescent [1,2] and phosphorescent ones, [3,4] are now recognized as third-generation electroluminescent materials for organic light-emitting diodes (OLEDs). [5][6][7][8] Thanks to the small energy difference (DE ST ) between the lowest singlet (S 1 )and triplet (T 1 )states,they can realize atheoretical 100 %internal quantum efficiency (IQE) through at hermally assisted reverse intersystem crossing from T 1 to S 1 .I n2 012, Adachi and co-workers prepared ag roup of carbazolyl dicyanobenzene derivatives, [9] and demonstrated that their delayed fluorescence efficiencies were comparable to those of phosphors.S ince then, much effort has been focused on the design of numerous TADF small molecules with efficient deep-blue to near-infrared emissions, [10][11][12][13] whose device fabrication relies on an expensive vacuum deposition technique.B yc ontrast, the development of TADF polymers,c apable of low-cost wet methods including spin-coating and inkjet printing,i ss till lagging behind in terms of amount and efficiency. [14,15] Generally,s everal principles could be adopted for the design of TADF polymers (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[19] The small-molecule D-A or D-p-A chromophores of various colors have achievedg ood performances so far,a nd considerable progress has been made in increasing the h ext values of red-green-blue (RGB) TADF OLEDs, for example, nearly 37 %f or sky-blue, [20] over 30 %f or green, [21] and 21-29.2 %f or orange-red. [22] To the best of our knowledge,t hese values should be state-of-art efficiency for each primary colored TADF OLED reporteds ofar.I tisclear that the electroluminescent properties of individual RGB-emitting TADF materials are efficient and stable, andh ave been successfully utilized in OLEDs.H owever,T ADF materials of similarm olecular skeletons, with emissions covering aw ide parto fo rt he entire visiblelight range have been rarely reported so far.I na ddition, many orange-red TADF emittersh ave played positiver oles in both single-color and white OLEDs,b ut only af ew materials can achieve high efficiency. [23] This is partially because the longwavelength emitters (orange to red) are generally subjected to increasing nonradiative internal conversion processes governed by the energy gap law,a nd resulting in low photoluminescenceq uantum yields (PLQYs, F PL ).…”
Section: Introductionmentioning
confidence: 99%